Arsenic solid-phase speciation and reversible binding in long-term contaminated soils. (February 2017) - Rahman, M.S.; Clark, M.W.; Yee, L.H.; Comarmond, M.J.; Payne, T.E.; Kappen, P.; Mokhber-Shahin, L.
Abstract: Historic arsenic contamination of soils occurs throughout the world from mining, industrial and agricultural activities. In Australia, the control of cattle ticks using arsenicals from the late 19th to mid 20th century has led to some 1600 contaminated sites in northern New South Wales. The effect of aging in As-mobility in two dip-site soil types, ferralitic and sandy soils, are investigated utilizing isotopic exchange techniques, and synchrotron X-ray adsorption spectroscopy (XAS). Findings show that historic soil arsenic is highly bound to the soils with >90% irreversibly bound. However, freshly added As (either added to historically loaded soils or pristine soils) has a significantly higher degree of As-accessibility. XAS data indicates that historic soil arsenic is dominated as Ca- (svenekite, & weilite), Al-(mansfieldite), and Fe- (scorodite) like mineral precipitates, whereas freshly added As is dominated by mineral adsorption surfaces, particularly the iron oxy-hydroxides (goethite and hematite), but also gibbsite and kaolin surfaces. SEM data further confirmed the presence of scorodite and mansfieldite formation in the historic contaminated soils. These data suggest that aging of historic soil-As has allowed neoformational mineral recrystallisation from surface sorption processes, which greatly reduces As-mobility and accessibility. Graphical abstract: Highlights: Isotope Exchange (IE) and XAS techniques combined are a powerful analytical tool. IE and XAS delineate chemically-labile As-forms, -sorbed and/or –free precipitates. Aging time is an important factor in determining the labile As in soil. SEM analysis confirms free precipitates of Al-, and Fe-arsenates.